One year efficacy and safety of oral sildenafil treatment in severe pulmonary hypertension - Samaržija, Miroslav; Žuljević, Ervin; Jakopović, Marko; Sever, Branko; Knežević, Aleksandar, liječnik; Đumija, Željko; Vidjak, Vinko; Šamija, Mirko (2009)
Abstract: Severe pulmonary hypertension is a progressive disease which leads to limitations of functional status and poor survival. We evaluated efficacy and safety of a short (3 months) and a long term (12 months) sildenafil treatment in patients with severe pulmonary hypertension. We treated 12 patients with pulmonary hypertension with oral sildenafil. Patients were followed at three time points, at baseline, and after 3 and 12 months of treatment. Primary end point was improvement in functional exercise capacity assesed by 6-minute walk test, and secondary end points were changes in right ventricle hemodynamics. We found significant improvement in 6-minute walk test distance from 357±193 m at baseline to 431±179 m after three months and further improvement to 501±159 m after 12 months (p<0.01); decrease in right ventricule pressure from 107±42 mmHg at baseline to 87±32 mmHg after 12 months (p<0.01); and, decrease in right ventricule diameter from 3.2±1.1cm to 2.76±0.86 cm after twelve months (p<0.01). Drug-related adverse events were mild and transient in our group of patients. Long term (12 months) sildenafil treatment is effective and safe in our patients with idiopathic and chronic thrombo-embolic pulmonary hypertension
Bibliografija: 47 jed
Sažetak
Keywords: Plućna hipertenzija -- Sildenafil